Delayed or on-time? Examining the moderating effect of academic timing on the relative age effect among Canadian interuniversity athletes. Issue 2 (4th May 2018) - Chittle, Laura; Horton, Sean; Dixon, Jess C.
ABSTRACT: Relative age effects (RAE) are developmental advantages experienced by those born in the initial months after a predetermined cut-off date over their younger counterparts. Student-athletes are considered to be "on-time" when their current year of athletic eligibility coincides with their expected year of athletic eligibility, based on their year of birth. Conversely, student-athletes are considered "delayed" when their current athletic eligibility year corresponds with a younger cohort. This study examined the impact of the RAE and academic timing on participation within nine of the 12 Canadian Interuniversity Sport (CIS) championship sports. A logistic regression was conducted to predict academic timing based on participants' quartile of birth and sex. The results indicated that males are significantly more likely to be delayed than females, and those student-athletes born in the later months of the year are more frequently delayed compared to their relatively older peers.